THEORETICAL FOUNDATIONS OF THE SMART CITIES DEVELOPMENT IN THE TRANSFORMATIONAL ECONOMY - Олешко, Анна А.; Чернаєнко, Данило В. (Journal of Strategic Economic Research, 2024)
The article examines the theoretical foundations of the development of smart cities of Ukraine in the transformational economy. In today’s world, which is rapidly transforming under the influence of technological innovations and deep economic changes, the concept of SMART cities is becoming a necessary link for sustainable development and effective management of urban spaces. The change in the economic landscape of Ukraine determines the need for active adaptation and innovative improvement of the urban environment. In this context, the concept of building SMART cities becomes a key strategic direction for sustainable development and introduction of advanced technologies in city management. The implementation of smart technologies in the urban environment is determined not only by achieving efficiency, but also by solving complex challenges for Ukraine in terms of implementing the mechanisms of intelligent urban systems. The purpose of the article is a theoretical analysis and generalization of the features and mechanisms of building SMART-cities in the conditions of the transformational economy. The article examines the theoretical basis of the development of SMART cities of Ukraine in the transformational economy based on the identification of key concepts, analysis of innovative models, forms and methods. The formation of the theoretical foundations of development is an initial component of the successful implementation of innovations in the urban environment. Understanding the essence of smart technologies and their impact on the economy and socio-cultural sphere is decisive for the creation of highly efficient, technologically mature cities that are able not only to adapt to changes, but also to actively contribute to their formation. It was concluded that the development of SMART cities in the context of the transformation of the economy involves the creation of a strategic innovation system for solving challenges and tasks in the era of global changes. This system provides for the smartization of the transport system, the implementation of energy-efficient solutions, the development of the health care system, the utility sector and other areas of the city economy.